2013
DOI: 10.1200/jco.2013.51.4315
|View full text |Cite
|
Sign up to set email alerts
|

Screening Alone Is Not Enough: The Importance of Appropriate Triage, Referral, and Evidence-Based Treatment of Distress and Common Problems

Abstract: See accompanying article on page 3631Hollingworth et al 1 are to be commended on their careful execution of this study, including an adequately powered sample size, long follow-up period, and the addition of a thorough economic analysis, which is rarely undertaken in the context of psychosocial interventions. This is particularly important in countries with nationalized health care systems such as the United Kingdom, where changes to practice may often be widely implemented without knowledge of the economic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 14 publications
2
54
0
3
Order By: Relevance
“…However, as recently suggested by Carlson regarding screening for distress [38], our study also required centers to define clearly the actions to adopt to ensure that psychosocial problem detection would be followed by appropriate interventions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as recently suggested by Carlson regarding screening for distress [38], our study also required centers to define clearly the actions to adopt to ensure that psychosocial problem detection would be followed by appropriate interventions.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, in their evaluation of psychosocial care in 11 outpatient medical oncology settings carried out in 11 practice sites in Florida, Jacobsen et al [37] found that emotional well-being was assessed in 52 % of cases, which is much lower than the 87 % adherence percentage obtained in our study. Many studies report various obstacles hindering screening implementation in practice, which include the lack of a screening strategy, and the lack of a management plan to ensure systematic response to screening results [36,38]. HuCare acted on these barriers by requiring centers to outline their own screening strategy, including aftercare following screening.…”
Section: Discussionmentioning
confidence: 98%
“…Wie Untersuchungen zeigten, ist das BT vergleichbar mit umfangreicheren Messinstrumenten sowie mit einem psychiatrischen GesprĂ€ch zur EinschĂ€tzung des Bedarfs an psychosozialer UnterstĂŒtzung (Mehnert et al, 2006;Vodermaier et al, 2009;Mitchell, 2010 (Carlson, Waller & Mitchell, 2012;Carlson, 2013;Donovan et al, 2014;Feldstain et al, 2014;Fulcher & Gosselin-Acomb, 2007;Gao et al, 2010;Holland et al, 2010;Mehnert et al, 2006;Söllner et al, 2001;Vodermaier et al, 2009 (Mergenthaler et al, 2011). Dennoch ermöglicht das AusfĂŒllen des BT im Rahmen eines professionellen AnamnesegesprĂ€chs, die BedĂŒrfnisse der Patient(inn)en vollstĂ€ndig zu erkennen, gezielte Interventionen einzuleiten oder eine Überweisung an Fachdienste durchzufĂŒhren (Carlson et al, 2012).…”
Section: Methoden Projektdesignunclassified
“…Das Fazit bestand allerdings darin, dass der Nutzen eines Screenings nicht nur vom Instrument, sondern vor allem von Ă€ußeren Bedingungen abhĂ€ngt, beispielsweise von der Nutzung (Mitchell, 2013). Wie Pflegende das Belastungs-Screening einsetzen, [WERT] (27) [WERT] (26) [WERT] (24) [WERT] (24) [WERT] (23) [WERT] (22) [WERT] (21 (Mehnert et al, 2006;Mitchell, 2007 (Carlson, 2013 …”
Section: Methoden Projektdesignunclassified
“…47 However, the effectiveness of screening for distress is disputed when it is used independent of a structured referral process or the development of a care plan. 48 Additionally, questions have been raised about whether patients receive appropriate support and access to services without screening.…”
Section: Clinical Utilitymentioning
confidence: 99%